Lipid metabolic dysregulation-induced neuroinflammation in the pathophysiology of major depressive disorder - Ge, Ziyu; Hu, Yongdong; Kan, Weijing; Li, Lei; Xu, Jiyi; Zhang, Yi; Zheng, Nan; Wang, Gang; Du, Jing (Frontiers in Immunology, 2025)
Depressive disorders exhibit significant comorbidity with lipid dysregulation. Clinical observations indicate that poor lifestyle factors contribute to lipid dysregulation in depressed patients. This dysregulation disrupts gut microbiota homeostasis and endocrine balance. Mitochondria and endoplasmic reticulum, critical organelles for lipid metabolism, also show impaired homeostasis in depression, further contributing to lipid dysregulation. Such alterations activate peripheral and central immune-inflammatory responses, compromise blood-brain barrier integrity, and disrupt neuroimmune cytokine signaling. This process induces and aggravates neuroinflammation, thereby contributing to the onset and progression of depressive disorders. These disruptions in homeostasis further exacerbate lipid dysregulation. This review delineates the molecular mechanisms by which dysregulation of lipid metabolism exacerbates depressive disorders via neuroinflammatory pathways, offering critical insights into pathogenesis and therapeutic strategies.